n=(4-1)*(4-2)*(4-3)*(4-4)*(4-5)*(4-6)/720

Simple and best practice solution for n=(4-1)*(4-2)*(4-3)*(4-4)*(4-5)*(4-6)/720 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for n=(4-1)*(4-2)*(4-3)*(4-4)*(4-5)*(4-6)/720 equation:



n=(4-1)(4-2)(4-3)(4-4)(4-5)(4-6)/720
We move all terms to the left:
n-((4-1)(4-2)(4-3)(4-4)(4-5)(4-6)/720)=0
We add all the numbers together, and all the variables
n-(3210(-1)(-2)/720)=0
We multiply parentheses ..
n-(3210()/720)=0
We multiply all the terms by the denominator
n*720)-(3210()=0
Wy multiply elements
720n^2=0
a = 720; b = 0; c = 0;
Δ = b2-4ac
Δ = 02-4·720·0
Δ = 0
Delta is equal to zero, so there is only one solution to the equation
Stosujemy wzór:
$n=\frac{-b}{2a}=\frac{0}{1440}=0$

See similar equations:

| n=(4+1)*(4+2)*(4+3)*(4+4)*(4+5)*(4+6)/720 | | .19-6q=q.q | | 6-5(4x+9)=8 | | 4x-9=83 | | |2–5x=7x–12| | | 4x-10=77 | | 3(3w-3)=-6w+27 | | 3(w-3)=6w | | (100/x)*x=(275,000/270,000) | | 8x-229=5x-91 | | (2y-5)+65=180 | | 12^x+6=11^5x | | 7x-6x+12=12-4 | | (1+i)(7−6i)=0 | | 6(t+11)=8(t-19) | | 450=450+10p | | 11+2x=21 | | 13-6t-16=6t+21-4t | | 3y-3y=48 | | 450=-300+10p | | -6x+17=7x+4 | | 5n+3=-2 | | 6/x+3=11/x-2 | | -10=y+6 | | 6x+32=104 | | -5x+18=68 | | -7x-2(11-x÷-2)=-13 | | (v-10)^3-40=0 | | 18=6(p+5) | | x/5+9=21 | | 4x+3=1;3x+2=2 | | -12=3.9c |

Equations solver categories